RANCANGAN OPTIMASI KONTROL PELAYANAN DI INSTALASI BEDAH SENTRAL RUMAH SAKIT UMUM DAERAH TUGUREJO SEMARANG - Arief Kurniadi (VISIKES: Jurnal Kesehatan Masyarakat, 2011)
Installation of the Central Surgical (IBS) Regional General Hospital Tugurejo Semarang in activities using the book service registers IBS and have been using a computerized system, but the information generated has not been able to meet the information needs, especially the number of operations according to the group and specializes in one month , average per day operation, the number of emergency operations per day, percentage of daily emergency operations, and income statements every month. Therefore required a more optimal system in controlling the service in IBS.The method used in the development of information systems is the method of system development life cycle or SDLC by stage of planning, system analysis until the design stage. With the method of data retrieval through obserasi and interviews to the Head of IBS Services Unit, Administrative Officer of IBS, IBS Nurse Service Unit, and Head Units installation inpatient services.The results of this study indicate that the perpetrators of system care information systems include desk clerk IBS, IBS Nurse, IRNA Officer and Head of IBS. Actors that perform activities, registration of the official IRNA, the input data list IBS patients by nurses, input details of the action IBS by administration officials, and received a report by the head of IBS. From observations and interviews with the actors produced system IBS computer-based information systems.Based on the results of the design of information systems that processed data is the data doctors, officers, sections, rooms and wards, rates and categories of action, and disease data. While the information generated is IBS service reports, earnings reports, and reports according to the type and number of surgical specialties, with the involvement of the IRNA, doctors, nurses IBS, head of IBS, IBS Administrative Officer, Head of Service Unit and theDirector.Key words: information systems, installation of central surgical